Sexual femicide, non-sexual femicide and rape: Where do the differences lie? A continuum in a pattern of violence against women - Zara, Georgia; Gino, Sarah; Veggi, Sara; Freilone, Franco (Frontiers in Psychology, 2022)
Violence against women is a growing health problem, especially when perpetrated in intimate relationships. Despite increasing attention, there is little comparative evidence on the different types of violence involved and there is a paucity of research on sexual femicides. This study examines cases of violence against women in northern Italy, focusing on sexual and non-sexual femicides and comparing them with rape that does not result in femicides. The sample included 500 women who were victims of sexual and non-sexual femicides, and of rape. Results show sexual femicides mostly involved unknown victims or women who were prostitutes. Sexual femicidal offenders used improper weapons to kill their victims, acted in secluded locations, and fled the crime scene; their crime was more likely the result of predatory intentions, with antisociality and sexual deviance being the most significant factors related to this type of femicide. The criminal and violent pattern that characterized sexual femicides in this study shared significant similarities with the pattern of violence involved in rape. Rape victims were in fact mostly unknown, or involved in a brief relationship with their killer. When the victim was known it was more likely that the abuse occurred at home and in front of the woman’s children. Rapists were often under the effect of alcohol or drugs. Non-sexual femicides mainly involved known victims, and they were more often committed in the context of domestic disputes. It was not seldom that the long relationship between the victim and perpetrator was likely to be characterized by contentiousness, suggesting that the woman was often victim of an oppressive climate of emotional tension and domination. Morbid jealousy contributed to aggravating the tone of a controlling relationship. Non-sexual femicides bore more similarities to cases of rape within the pattern of intimate partner violence. Findings are discussed in terms of their implications for prevention and intervention.